Age, depositional history and tectonics of the Indo-Burman ranges - Naing, TT (2019)
This thesis examines the provenance and depositional processes of the sedimentary rocks of the Indo-Burman Ranges (IBR), discusses the tectonic evolution of the IBR, and provides a synthesis of the geological evolution of Myanmar. The IBR form an enigmatic mountain belt, comprising a western belt of folded and thrusted mainly Cenozoic sedimentary rocks, a central zone of highly deformed Triassic turbidites (Pane Chaung Formation) and low-grade metamorphic rocks (Kanpetlet Schist), and an eastern zone comprising a major Neo-Tethyan suture zone. The newly discovered early Jurassic-early Cretaceous radiolarian assemblages from ophiolitic mélange in the Kalemyo area and late Paleocene-early Eocene radiolarian ages from the Ngapali mélange, with ages similar to those of the Indus – Yarlung Tsangpo suture zone of south Tibet and Nagaland, reinforces the hypothesis that the Kalemyo - Nagaland suture and Indus – Yarlung Tsangpo suture represent a single suture zone that separates the Indian plate to the west (IBR) and Asian plate to the east (Central Basin and Wuntho-Popa Arc). The data presented suggest that Triassic turbidites were originally deposited on the northeastern India (Gondwana) margin, not the Asian (Sibumasu) plate, and that a wide Neo-Tethyan ocean separated the IBR from the Wuntho-Popa Arc (WPA) and the Shan Plateau. The geochemistry of detrital zircons from Upper Cretaceous sedimentary rocks of the IBR to be derived predominantly from the core of the IBR where marks a broad suture zone. Similar data from the Paleocene-Eocene flysch sediments suggest derivation from the Wuntho-Popa Arc and the core of the IBR.